Preparation and Properties of NrGO-CNT Composite for Lithium-Ion Capacitors. Issue 14 (1st January 2017) - Wang, Jeng-An; Li, Shin-Ming; Wang, Yu-Sheng; Lan, Pei-Yu; Liao, Wei-Hao; Hsiao, Sheng-Tsung; Lin, Sheng-Chi; Lin, Chih-Wen; Ma, Chen-Chi M.; Hu, Chi-Chang
Abstract : The lithium-ion capacitor (LIC), combining the advantages of lithium-ion batteries and supercapacitors, has gained significant attention as a new class of energy storage system. Typically, the LIC consists of graphite as the negative electrode and activated carbon (AC) as the positive electrode, while the energy density is limited by the low capacitance of the positive electrode. In this study, an innovative composite material of nitrogen-doped reduced graphene oxide (NrGO) chemically bonded with carbon nanotubes (CNTs), denoted [NrGO-CNT], is designed to circumvent this issue. The [NrGO-CNT] composite possesses not only high electrical conductivity but also high specific surface area and well-distributed mesopores and micropores. The LIC employing [NrGO-CNT] composite shows a cell capacitance retention of 93.5% after 1000 cycles at a scan rate of 200 mV s −1, revealing high cycling stability. This LIC delivers a high specific energy of 124.9 Wh kg −1 at a specific power of 1.26 kW kg −1 at the cell voltages between 1.5 and 4.5 V. Consequently, the [NrGO-CNT] composite is a promising electrode material for high-performance LICs.